Localising Environmental Governance: The Le Sueur Case - Humbly, Tracy-Lynn (Potchefstroom Electronic Law Journal, 2017)
In the matter of Le Sueur v Ethekwini Municipality the KwaZulu-Natal High Court decided that municipalities had the power to legislate on environmental issues such as biodiversity and conservation. This note argues that the precedent established in this case is that municipalities have authority to legislate upon environmental matters as an incident of municipal planning, which is an original constitutional power. In contrast to both the judgment and recent commentary, it argues that the source of municipal legislative authority over municipal planning is not based in legislative assignment but in s 156(5) of the Constitution (the "incidental power" provision relevant to local government). This argument is based on understanding the distinction between original and assigned powers, and the nature of the control that the national and provincial spheres exercise over Schedule 4B powers. Notwithstanding this inaccuracy in the judgment, it is argued that the precedent is a welcome one that can be justified not only on the basis of the principle of subsidiarity but also in terms of the emerging and increasingly important theory of social-ecological resilience.